The Dhuha Prayer and Students’ Emotional and Character Development : A Psychospiritual Phenomenological Inquiry - Ramadhani, Zhafira; Hana Kamilah; Puteri Muslihatul Ummah; Rifatul Hasanah; Fikron Yunus; Abdul Fadhil (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
This study examines how students of the Islamic Education Department (PAI) at FISH UNJ interpret the role of the Duha prayer in supporting emotional balance and character formation. Using a qualitative approach with a phenomenological perspective, the research focuses on students’ lived experiences and the changes they notice after regularly performing the Duha prayer. Data were gathered through interviews, observations, and documentation. The study found that the Duha prayer is perceived not only as a recommended religious practice, but also as a moment that helps students organize their thoughts, reduce academic pressure, and manage emotional challenges within the campus environment. The habit of performing the prayer is also associated with the development of discipline, calmness, and a greater sense of responsibility. These findings suggest that the Duha prayer can serve as a meaningful practice that supports students in maintaining emotional stability and strengthening positive character.